Remote climate forcing of decadal‐scale regime shifts in Northwest Atlantic shelf ecosystems. (3rd May 2013) - Greene, Charles H.; Meyer-Gutbrod, Erin; Monger, Bruce C.; McGarry, Louise P.; Pershing, Andrew J.; Belkin, Igor M.; Fratantoni, Paula S.; Mountain, David G.; Pickart, Robert S.; Proshutinsky, Andrey; Ji, Rubao; Bisagni, James J.; et al.
Abstract : Decadal‐scale regime shifts in Northwest Atlantic shelf ecosystems can be remotely forced by climate‐associated atmosphere‐ocean interactions in the North Atlantic and Arctic Ocean Basins. This remote climate forcing is mediated primarily by basin‐ and hemispheric‐scale changes in ocean circulation. We review and synthesize results from process‐oriented field studies and retrospective analyses of time‐series data to document the linkages between climate, ocean circulation, and ecosystem dynamics. Bottom‐up forcing associated with climate plays a prominent role in the dynamics of these ecosystems, comparable in importance to that of top‐down forcing associated with commercial fishing. A broad perspective, one encompassing the effects of basin‐ and hemispheric‐scale climate processes on marine ecosystems, will be critical to the sustainable management of marine living resources in the Northwest Atlantic.